2014
DOI: 10.1111/eea.12262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three endophytic entomopathogens on sweet sorghum and on the larvae of the stalk borer Sesamia nonagrioides

Abstract: Various endophytic fungi of native plants and crops are important entomopathogens. The objective of this study was to investigate the entomopathogenic action of Beauveria bassiana (Balsamo) Vuillemin, Metarhizium robertsii (Metchnikoff) Sorokin, and Isaria fumosorosea (Wize) Brown & Smith (all Ascomycota: Hypocreales) against larvae of Sesamia nonagrioides (Lefebvre) (Lepidoptera: Noctuidae) artificially introduced into Sorghum bicolor L. (Moench) (Poaceae) plants under natural environmental conditions. Sorghu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
72
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 45 publications
(69 reference statements)
9
72
0
4
Order By: Relevance
“…Reduction in larval population and reduced damage may be associated with endophytic colonization of B. bassiana. Similar results were reported with endophytic B. bassiana strains for European corn borer, Ostrinia nubilalis in maize (Bing and Lewis, 1991), Sesamia calamistis in maize (Cherry et al, 2004), Cosmopolites sordidus in banana (Akello et al, 2008), Sesamia nonagrioides in sorghum (Mantzoukas et al, 2015) and Helicoverpa armigera in tomato (Qayyum et al, 2015). It has been reported (Gurulingappa et al, 2011) that endophytic strains of B. bassiana might have produced certain secondary metabolites in the host plant with anti feeding properties and insecticidal activity against the pests leading to mortality/less activity of the pest.…”
Section: Effect Of Endophytic Beauveria Bassiana Strains On Infestatisupporting
confidence: 81%
“…Reduction in larval population and reduced damage may be associated with endophytic colonization of B. bassiana. Similar results were reported with endophytic B. bassiana strains for European corn borer, Ostrinia nubilalis in maize (Bing and Lewis, 1991), Sesamia calamistis in maize (Cherry et al, 2004), Cosmopolites sordidus in banana (Akello et al, 2008), Sesamia nonagrioides in sorghum (Mantzoukas et al, 2015) and Helicoverpa armigera in tomato (Qayyum et al, 2015). It has been reported (Gurulingappa et al, 2011) that endophytic strains of B. bassiana might have produced certain secondary metabolites in the host plant with anti feeding properties and insecticidal activity against the pests leading to mortality/less activity of the pest.…”
Section: Effect Of Endophytic Beauveria Bassiana Strains On Infestatisupporting
confidence: 81%
“…According to Tefera and Vidal (2009), spraying with conidial suspensions of B. bassiana was the best method for introducing the fungus into sorghum leaves. When a B. bassiana conidia solution was sprayed onto maize, the fungus colonized the leaves and translocated to other tissues (Wagner and Lewis 2000 in Mantzoukas et al 2015). Once hyphae on the leaf surface penetrate the cuticle, they follow the leaf apoplast and move through interconnected vascular tissues to colonize the entire plant (Mantzoukas et al 2015).…”
Section: Colonization By B Bassianamentioning
confidence: 99%
“…, Mantzoukas et al. , also see references reviewed by Vidal and Jaber ). The majority of these studies revealed that endophytic B. bassiana reduces herbivore damage by a wide range of sucking, chewing, and tunneling insects in leaves and stems (Vidal and Jaber ).…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, endophytic I. fumosorosea in sweet sorghum was found to greatly increase larval mortality of the stem borer Sesamia nonagrioides and reduce stem‐tunneling activities by 60–87% (Mantzoukas et al. ). Although M. alpina and F .…”
Section: Discussionmentioning
confidence: 99%